1. Musical Abilities Very Early in Life - Iuşcă Dorina Geta (Sciendo, 2023)
Music-related skills are not always an effect of systematic music education. Many music perception acquisitions develop naturally due to children's exposure to melodic and rhythmical structures across their life. Experts found that even at very early stages of life, children are capable of identifying and differentiating musical structures. More so, they develop musical preferences closely related to certain biological features or certain emotional aspects regarding their relationship with their mother. The present study aims to review the latest findings associated to these musical skills that occur during the prenatal period and the first year of life.